Anatomical, Histological and Histochemical Investigation of Soft Palate in Cat (Felis Catus Domesticus.L) (Indian Journal of Forensic Medicine & Toxicology, 2020)
Objectives: The aim of this study was to evaluate the normal structure and provide distribution for palatineglands in cranial and caudal part of soft palate. Also, afford information to be useful for both surgicalinterventions and pathological disease. Method/: Sixth healthy cats were caught in Iraq farms. All experimentalanimals euthanized by intramuscular injection of ketamine (0.5 cc) and xylazine (0.5 cc), Sections werestained by H&E and combined AB+PAS stain 2.5 pH. Results: The soft palate was triangular in shape, thedimensions was (2.8, 2) cm in length and width respectively. Also, had two surface; nasopharyngeal surfacelined by psuedostratified columnar epithelial ciliated and oropharyngeal surface lined by stratified squamousepithelia. The palatine glands appeared magenta in color during staining by AB+PAS combined stain dueto neutral secretion. Conclusion: The palatine glands variance in distribution between dorsal and ventralsurface of soft palate, most of these glands constricted in oropharyngeal surface.